Computational fluid dynamics (CFD) simulation of triple exposure solar oven / Mohd Fadhli Mat Zain and Fauziah Jerai@Junaidi - Mat Zain, Mohd Fadhli; Jerai@Junaidi, Fauziah (2010)
This study presents the simulation study on triple exposure of solar oven, which inspired on design features from common solar oven that has been used widely by some places in this world. Some deficient in renewable energy is contributed on this study to find a new solution to maximize utilization of renewable energy in our daily life. The objective of this project is to determine the distribution of temperature air inside of solar oven for a period of time. This triple exposure represent that the glass oven have three surfaces to be exposed on solar radiation. The simulation is conducted using Computational Fluid Dynamic (CFD) software, CD ADAPCO STAR-CCM+. The duration time of the solar oven exposed to the solar radiation is due to the total normal daylight time which estimated from 8 am to 6 pm. Therefore, the CFD simulation is simulate by each an hour from the total hour was exposed to the solar radiation. In order to validate the CFD results, theoretical analysis of triple exposure solar oven was calculated to obtain the result. The results show that the distribution of temperature air inside of triple exposure solar oven by CFD shows a fairly good agreement with the theoretical results. The results obtained will be useful as additional database on the study of triple exposure solar oven.